1999
DOI: 10.1080/13668809908412187
|View full text |Cite
|
Sign up to set email alerts
|

A best case scenario? Non-manual part-time work and job-sharing in UK local government in the 1990s

Abstract: Local authorities in the UK have been described as 'model employers' of part-time and job-share employees, with the needs of employees themselves, particularly women with family responsibilities, acting as the primary driver for the use of reduced hours working patterns. To investigate how far this 'exemplar' label applied in practice, and to what extent this overcame the well-known drawbacks of reduced hours working patterns, the causes and consequences of working reduced hours amongst professional, manageria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, in reality, WLB remains elusive, with studies often finding 'imbalance' (Bloom, 2016). In the UK WLB policy and practice is based on potential economic benefits (Stanworth, 1999;Taylor, 2002), also reflected in the findings of Crompton et al's (2008) European study that links WLB with a happier workforce, reduced absenteeism, increased retention and productivity.…”
Section: Work-life Balancementioning
confidence: 99%
“…However, in reality, WLB remains elusive, with studies often finding 'imbalance' (Bloom, 2016). In the UK WLB policy and practice is based on potential economic benefits (Stanworth, 1999;Taylor, 2002), also reflected in the findings of Crompton et al's (2008) European study that links WLB with a happier workforce, reduced absenteeism, increased retention and productivity.…”
Section: Work-life Balancementioning
confidence: 99%
“…A challenge associated with part-time work is that managers might not always adjust expectations correctly when employees move from full- to part-time positions, thus influencing the effectiveness of flexible work policies (Stanworth 1999). For instance, working reduced hours often means having to deal in a shorter time with what effectively remains a full-time workload (Edwards and Robinson 2000; Lewis 2001, 2003), a phenomenon that could lead to a gap between productivity and wages of part-time workers.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Likewise, Ahuja and Carley (1998) found that many virtual organizations were quite hierarchical in their communication processes, even where information seeking was involved. Electronic networking has the capacity to allow both great autonomy and flexibility and increased managerial control and surveillance (Stanworth, 1999). Harrison and Falvey (2001, p. 24) argued that "new technologies are far more frequently used to gather information about employees than they are appropriated by employees for their own purposes."…”
Section: Information and Communication Technologymentioning
confidence: 99%